Implementation of Kegiatan Keputrian in Enhancing Female Students' Understanding of Fiqh of Worship at SMP Swasta Islam Terpadu Indah Medan - Nur Azizah; Sokon Saragih (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the implementation of girls’ activities and their role in improving female students’ understanding of fiqh of worship at SMP Swasta Islam Terpadu Indah Medan. The study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, which includes data collection, data reduction, data display, and drawing conclusions. The results show that the girls’ activities are held regularly every Friday. The topics covered include fiqh of worship such as purification, menstruation, prayer, and fasting, taught using lectures, discussions, question-and-answer sessions, demonstrations, and teaching media such as PowerPoint and related videos. The girls’ activities play a role in improving students’ understanding of fiqh of worship, as evidenced by an increased ability of the students to understand and apply worship procedures according to Islamic law. Supporting factors include school support, supervising teachers, adequate facilities and infrastructure, and students’ enthusiasm. Inhibiting factors include limited time for implementation and differences in students’ levels of understanding. Thus, the girls’ activities are an effective development program for improving female students’ understanding of fiqh of worship.